"WHEN WILL THIS NONSENSE END?": BARRIERS TO IMPLEMENTING THE PELI AMONG OHIO NHS. (11th November 2018) - Abbott, K M; Leser, K; Liddic, M; Straker, J; VanHaitsma, K S
Abstract: The Preferences for Everyday Living Inventory (PELI) was selected as pay for performance quality indicator for nursing homes by the Ohio Department of Medicaid in 2015. A state wide Qualtrics questionnaire conducted in 2016 with n=964 nursing home providers sought to identify the barriers to implementing the PELI. Results: Major barriers reported by providers included: resident unable to complete interview due to cognitive impairment (76%), resident not having a family member or proxy to interview (70%), resident refuses to complete the interview (64%), and lack of time for staff to conduct the interviews (61%). Minor barriers included lack of guidance/information about how to use the PELI to guide care (41%), staff turnover (37%), staff resistance/lack of interest (34%), and lack of trained staff to conduct the interviews (31%). Discussion: Potential ways to remediate barriers to providing person-centered care will be discussed as well as implications for practice and research.